2004
DOI: 10.4049/jimmunol.173.7.4618
|View full text |Cite
|
Sign up to set email alerts
|

A Nonneutralizing Anti-HIV-1 Antibody Turns into a Neutralizing Antibody When Expressed on the Surface of HIV-1-Susceptible Cells: A New Way to Fight HIV

Abstract: During HIV-1 infection or vaccination, HIV-1 envelope spikes elicit Ab responses. Neutralizing Abs block viral entry by recognizing epitopes on spikes critical for their interaction with receptor, coreceptors or fusion. In contrast, nonneutralizing Abs fail to do so because they recognize epitopes either buried or exposed but not critical for viral entry. Previously, we produced a high-affinity human mAb against the cluster II determinant of gp41. This Ab or its recombinant Fab and single-chain Fv have been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…The experiment has been repeated three more times with similar results. Therefore, similar to what was found previously, 17 these results indicated that the m-scFv specifically targets the HIV-1 envelope.…”
Section: Inhibit Free Hiv-1 Pseudotype Infection In a Single-cycle Insupporting
confidence: 91%
See 3 more Smart Citations
“…The experiment has been repeated three more times with similar results. Therefore, similar to what was found previously, 17 these results indicated that the m-scFv specifically targets the HIV-1 envelope.…”
Section: Inhibit Free Hiv-1 Pseudotype Infection In a Single-cycle Insupporting
confidence: 91%
“…2D). These results indicated that the m-scFv not only can inhibit laboratory-adapted HIV-1 strains as shown in a previous report, 17 but it also can effectively inhibit primary isolates. Moreover, although the monoclonal antibody (TG15) (from which the m-scFv was derived) was originally derived from a human B cell hybridoma generated from a subtype B HIV-1-infected individual, it not only neutralizes HIV-1 from B subtypes (shown in the previous studies 17 as well as studies with LEE ET AL.…”
Section: Inhibition Of Viral Replication Of Primary Hiv-1 Isolates Bysupporting
confidence: 68%
See 2 more Smart Citations
“…Antibody directed against ␤-actin served as a protein loading control. Initially, infections of the TRIM5 expressing and control cells were performed with increasing amounts (2 to 100 ng) of HIV-GFP/VSV pseudotyped virus (51). Two days after infection, the cells were analyzed by flow cytometry for green fluorescent protein (GFP) expression.…”
Section: Methodsmentioning
confidence: 99%